Panic Buying and Environmental Disasters Management and Mitigation Approaches - Arafat, S.M. Yasir; Kumar Kar, Sujita; Kabir, Russell (Cham : Springer International Publishing : Imprint: Springer, 2022)
Panic buying is a common response during crises; however, to date it has been a significantly under-researched area. Recent evidence suggests that an environmental stimulus, such as the COVID-19 pandemic, war, earthquakes, flooding, public health emergencies (SARS, MARS) can trigger this phenomenon. As an environmental crisis takes its toll, the understanding of panic buying becomes overlooked. Nevertheless, panic buying causes series of events separate from these primary events. Understanding the management of emergencies and disasters should be an integral part of dealing with panic buying since every major environmental crisis has the potential to initiate panic buying behaviour in the general public. This book will analyse episodes of panic buying and major environmental crisis focusing on specific prevention strategies. This book is a groundbreaking approach to join up the management of panic buying during a public health emergency.
The Concept of and Risk Factors for Panic Buying -- Behavioral Events during Environmental Disasters -- Panic Buying and its Intrinsic Connection to Disaster -- Social Structure, Security, Disaster and Panic Buying -- Disaster, Health and Panic Buying -- Disaster and Consumption Behavior -- From Molecules to The Marketplace: The Theoretical Basis for Panic Buying Behavior during Disaster -- Characteristics of Panic Buying During Disaster: Pre-disaster, disaster and post disaster phase -- Communication during Disasters: Role in Contributing to and Prevention of Panic Buying -- Disaster, Public Health and Panic Buying -- Measurement of Panic Buying in Individual 1 and Social Level -- Prevention Strategies of Panic Buying during Disaster -- Disaster Preparedness and Panic Buying -- Disaster, e-Commerce and Panic Buying -- Public Health Administration in Controlling Panic Buying during Disaster -- Artificial Intelligence and Prevention of Panic Buying during Disasters -- Panic Buying and Special Conditions during Disasters -- Panic Buying and Health Literacy During Environmental Disasters.
Keywords: Psychology, Industrial; Consumer behavior; Social psychology; Industrial Psychology; Consumer Behavior .; Social Psychology; Organizational Psychology; Work and Organizational Psychology